Hubungan Pengetahuan Dan Sikap Wanita Usia Reproduktif Dalam Pemilihan Kontrasepsi IUD Di Puskesmas Temindung Samarinda Tahun 2017 - Fidiani, Datin; Chasanah, Siti Noor; Fijri, Bayu (Akademi Kebidanan Bunga Husada Samarinda, 2019)
IUDs have been proven to be more than 99% effective in preventing pregnancy. Most in developing countries where it is used by 14.5% of older women. In developed countries, this percentage is only 7.6%. In a preliminary study through interviews with acceptors, the researchers found that many mothers were reluctant to use an IUD because of excessive vaginal discharge, pain during intercourse, and fear of pain when IUD compilation was installed.IUD at Temindung Samarinda Health Center.The design of this research is quantitative cross sectional. The sample in this study was 99 using purposive random sampling. Data analysis using univariate and bivariate using SPSS.The results showed that there was a significant relationship between Knowledge of the Family Planning Method (P value of 0,000), there was a significant relationship between the Method of Attitude Toward Family Planning (P value 0.033).The recommendations of this study contribute to the Temindung Puskesmas and Midwives in the work area, in order to improve family planning services to improve IUD counseling.